THE IMPLEMENTATION OF CHU WANGHUA’S PIANO MUSIC FOR IMPROVISED ACCOMPANIMENT IN THE TEACHING OF MUSIC EDUCATION MAJORS AT CHINESE UNIVERSITIES - Lian, Kaikai; Sornyai, Phiphat (International Online Journal of Education and Teaching, 2023)
The objective of this study is to find out how improvisational accompaniment classes are taught in Chinese universities for music education majors and to come up with ways to use Chinese composer Chu Wanghua’s piano pieces. The Northeast Normal University, Beijing Normal University, and Fujian Normal University will be chosen as research sites for this study because they are three of the most important universities in China. A qualitative questionnaire survey is used. The teachers and students at the three universities who have been teaching improvising accompaniment for at least 25 years are the main sources of information for this research. The result of this study found that there are many problems with improvisational accompaniment in Chinese universities, such as weak piano performance skills, poor reading notation, a lack of polyphonic thinking and inner hearing, and too much emphasis on major and minor songs and too little on folk songs. The textbook is outdated and lacks analyses of folk song accompaniment. The teachers have not trained the students’ keyboarding ability from the beginning to the end, and homework is completed in written form, which seriously affects the development of students’ keyboard skills. To improve students’ ability to play improvisation accompaniment, the researcher believes that they should attach importance to the arrangement of content, increase the knowledge of Chinese pentatonic harmony in the teaching process, and increase the example analysis of Chinese piano music. This study takes the piano works of Chu Wanghua as an example and applies it to the teaching process, from piano performance to harmonic analysis.